Capital for concentrated credit portfolios - Paul H. Kupiec (American Enterprise Institute (AEI), 2015)
Most credit portfolios contain obligor concentration risk and yet international bank regulatory capital rules and many industry models assume perfect diversification. Multiple methods are available to calculate the approximate capital needs of a concentrated credit portfolio, but many of these involve advanced mathematical arguments, substantial computation time, and fail to clearly identify the most important credits causing concentration risk. In this article, I illustrate three approaches for calculating loss distributions and value-at-risk capital requirements. Of these, the large exposure approach proposed by Kupiec (2015) is especially easy to implement. It produces accurate estimates of the economic capital required for a concentrated portfolio and immediately identifies the obligors most responsible for generating concentration risk.
Keywords: A; 330; capital requirements; Basel Comittee on Banking Supervision